Critical Thinking: From Psychological Perspectives To Pedagogical Prospectives In Efl Teaching Contexts - Gunadi Harry Sulistyo (PROCEEDING UMSURABAYA, 2019)
Critical thinking is necessary and therefore it is considered to be an essential mental attribute that students must master. It was once a means that was needed to be learned in order for a nation at risk not to degrade intellectually. Now, the teaching of critical thinking skills has shifted in orientation from saving a nation from intellectual degradation to equipping students with necessary skills required to survive in the next millenium. English as a school subject can contribute significantly to the empowerment of students in facing the 21st Century with critical thinking skills. Pedagogical approaches fitting the characteristics of critical thinking skills are there available. If so, then it is the critical role of EFL teachers to harness their students with critical thinking skills – the fifth skills in language learning – through their innovative and creative teaching delivery that really matters.Keywords: English, critical, learning, skills, thinking